1998
DOI: 10.1212/wnl.51.4.1046
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic hamartomas and gelastic epilepsy

Abstract: We found no detectable neuronal damage in the temporal lobes of patients with hypothalamic hamartomas and gelastic epilepsy. This is further evidence that gelastic seizures do not originate in the temporal lobes of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1
6

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 8 publications
2
23
1
6
Order By: Relevance
“…The relative intensities of the NAA/Cr and the NAA/Cho ratios were not significantly different from those found in the temporal lobes of healthy volunteers. Within the HH, the NAA/Cho ratio was decreased; however, contrary to the findings of Tasch et al, 105 the NAA/Cr ratio was greatly increased in the aforementioned patient. 87 Other small studies have reported similar findings.…”
Section: Magnetic Resonance Spectroscopycontrasting
confidence: 85%
See 1 more Smart Citation
“…The relative intensities of the NAA/Cr and the NAA/Cho ratios were not significantly different from those found in the temporal lobes of healthy volunteers. Within the HH, the NAA/Cho ratio was decreased; however, contrary to the findings of Tasch et al, 105 the NAA/Cr ratio was greatly increased in the aforementioned patient. 87 Other small studies have reported similar findings.…”
Section: Magnetic Resonance Spectroscopycontrasting
confidence: 85%
“…Nine published reports with a total of 44 patients have described the MRS findings evaluating the NAA, Cr, Cho, and mI content within the hamartoma. The group in Montreal was the first to study the extent of neuronal injury in the temporal lobes and hamartomas of 5 patients with HHs and gelastic seizures by using proton MRS. 105 The NAA/Cr ratio was significantly decreased in the patients with hamartomas compared with the hypothalami of healthy individuals. Likewise, Pascual-Castroviejo et al 87 used MRS to study the temporal lobes and the HH in 1 patient.…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 90%
“…It was not until Cascino et al [13]published their unsuccessful results with subdural recording-guided corticectomies in 7 patients with HH and GS that neurologists and epilepsy surgeons understood that subdural telemetry data are misleading in HH. A similar experience was later described by Kuzniecky et al [12], who, with other investigators, presented new data provided by more sophisticated methodology, including ictal SPECT, monitoring with depth electrodes [12, 15]and MRS study [24], all of which pointing to the HH as the site of the epileptic focus.…”
Section: Discussionmentioning
confidence: 76%
“…8,14,15,20,23) In all cases the goal of the treatment was the removal of the entire lesion since it is commonly agreed that the hamartoma is the trigger of the epilepsy 3,5,7,8,11,13,21) and so the resection of hypothalamic hamartoma must be as complete as possible to achieve good seizure remission. 16) The present study suggests that complete removal of the hamartoma can be replaced by disconnection, using either open surgery or endoscopy, since the hamartoma is a stable lesion and entire anatomical removal is not necessary to treat the epilepsy.…”
Section: Discussion I Surgical Approaches and Techniquesmentioning
confidence: 99%